The Acceptance/Avoidance-Promoting Experiences Questionnaire (APEQ): A theory-based approach to psychedelic drugs' effects on psychological flexibility. (March 2022) - Wolff, Max; Mertens, Lea J; Walter, Marie; Enge, Sören; Evens, Ricarda
Background: Many benefits and some harms associated with psychedelic use could be attributable to these drugs' acceptance/avoidance-promoting effects and corresponding changes in psychological flexibility. Underlying psychological mechanisms are insufficiently understood. Aim: The purpose of this study was the validation of a psychological model of acceptance/avoidance-promoting psychedelic experiences, which included the development of a theory-based self-report instrument: the Acceptance/Avoidance-Promoting Experiences Questionnaire (APEQ). Its two main scales, acceptance-related experience (ACE) and avoidance-related experience (AVE), represent the theorized model's core constructs. We aimed to test the model's central assumptions of complementarity (ACE and AVE may occur alternatingly but not simultaneously, and are therefore empirically independent), intertwinedness (subaspects within ACE and AVE are mutually contingent and therefore highly inter-correlated), context-dependence (ACE and AVE depend on context factors) and interaction (longer-term outcomes depend on the interplay between ACE and AVE). Method: A bilingual retrospective online survey including 997 English- and 836 German-speaking participants. Each participant reported on one psychedelic experience occasioned by lysergic acid diethylamide (LSD), psilocybin, mescaline, or ayahuasca. Results: Whereas ACE and AVE were found to be relatively independent aspects of participants' reported psychedelic experiences (complementarity), their subaspects were mostly distinguishable but strongly correlated among each other (intertwinedness). Therapeutic, escapist, and hedonic use motives were differentially associated with ACE and AVE (context-dependence), which were in turn associated with retrospective changes in psychological flexibility following participants' reported experiences. The positive association between ACE and increased psychological flexibility was significantly moderated by AVE (interaction). Conclusion: These results provide an initial validation of the APEQ and its underlying theoretical model, suggesting the two can help clarify the psychological mechanisms of psychedelic-induced benefits and harms. Both should be further investigated in prospective-longitudinal and clinical studies.